Biochemical and structural characterization of the BioZ enzyme engaged in bacterial biotin synthesis pathway - Sitao Zhang (Nature Portfolio, 2021)
Biotin is an essential enzyme cofactor and two pathways for the generation of the biotin precursor pimeloyl-ACP are known. Here, the authors identify and characterize a third pathway for biotin precursor synthesis involving BioZ and they also present the Agrobacterium tumefaciens BioZ crystal structure.